Selective killing of p53-deficient cancer cells by SP600125 - Jemaà, Mohamed (WILEY-VCH Verlag, 2012)
The genetic or functional inactivation of p53 is highly prevalent in human cancers. Using high-content videomicroscopy based on fluorescent TP53(+/+) and TP53(−/−) human colon carcinoma cells, we discovered that SP600125, a broad-spectrum serine/threonine kinase inhibitor, kills p53-deficient cells more efficiently than their p53-proficient counterparts, in vitro. Similar observations were obtained in vivo, in mice carrying p53-deficient and -proficient human xenografts. Such a preferential cytotoxicity could be attributed to the failure of p53-deficient cells to undergo cell cycle arrest in response to SP600125. TP53(−/−) (but not TP53(+/+)) cells treated with SP600125 became polyploid upon mitotic abortion and progressively succumbed to mitochondrial apoptosis. The expression of an SP600125-resistant variant of the mitotic kinase MPS1 in TP53(−/−) cells reduced SP600125-induced polyploidization. Thus, by targeting MPS1, SP600125 triggers a polyploidization program that cannot be sustained by TP53(−/−) cells, resulting in the activation of mitotic catastrophe, an oncosuppressive mechanism for the eradication of mitosis-incompetent cells.